2013
DOI: 10.1007/s12306-013-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging assessment of groin pain

Abstract: Groin pain is a common condition in athletes, especially those who play certain sports, for instance soccer, ice hockey, fencing which request rapid acceleration and frequent changes of movement. This condition represents a diagnostic difficulty for the radiologist due to either the anatomical pubic region complexity than the many causes that can be a source of pain, because the groin pain can be determined by conditions affecting the bony structures, cartilage and muscle tendons that are part of the proper pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Hernia bulge may cause muscle tear and hemorrhage, inguinal nerve irritation, adjacent pubic bone irritation or radiating scrotal pain. Muscle tears, hemorrhage and edema around pubic structures (BME) should be detected in preoperative MRI [4]. Our earlier studies have shown some correlation between groin pain and the intensity of BME in elite athletes and physically active adults [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hernia bulge may cause muscle tear and hemorrhage, inguinal nerve irritation, adjacent pubic bone irritation or radiating scrotal pain. Muscle tears, hemorrhage and edema around pubic structures (BME) should be detected in preoperative MRI [4]. Our earlier studies have shown some correlation between groin pain and the intensity of BME in elite athletes and physically active adults [21].…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic MRI reliably shows bone fractures, including stress fractures, early arthrosis in the hip joint, bursitis and other causes of groin pain. Also sudden muscle tears with hemorrhage or edema may sometimes be associated with incipient inguinal hernia, and these are easily diagnosed using MRI [4]. MRI can also be used to grade bone marrow edema (BME) around pubic symphysis, and it can also detect other structural bone changes earlier than standard radiographs, for example, osteoarthritis and osteitis pubis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some who propose ultrasound as the imaging of choice believe that a sports hernia only can be diagnosed when, while straining the abdomen, a bulge of the posterior inguinal wall is visualized by ultrasound (15,17).…”
Section: Groin Injury and Imagingmentioning
confidence: 99%
“…wrote that this syndrome frequently occurs in football and accounts for 10-13% of all accidents every year (1). Since the onset of the syndrome in football, most specialists have approached this problem from a pharmacological, imaging, radiological and surgical point of view (2,3,4,5,6). A small number of specialists also addressed the issue of musculoskeletal impairment, syndrome classification, incidence and rehabilitation programs (7,8,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%